Overexpansion of older generation balloon expandable transcatheter heart valves: An ex‐vivo bench study. Issue 6 (9th March 2019) - Sathananthan, Janarthanan; Sellers, Stephanie; Barlow, Aaron; Hensey, Mark; Landes, Uri; Cheung, Anson; Ye, Jian; Alkhodair, Abdullah; Blanke, Philipp; Søndergaard, Lars; Pibarot, Phillippe; Wood, David; et al.
ABSTRACT: Background: The SAPIEN 3 (S3) transcatheter heart valve (THV) can be over‐expanded beyond its labeled diameter. Overexpansion can be achieved with use of either a compliant or non‐compliant balloon. Objective data regarding the ability to over‐expand older generation balloon expandable valves are limited. We sought to assess the effects of over‐expanding the SAPIEN and SAPIEN XT (Edwards Lifesciences, Irvine, CA) valve beyond labeled size (diameter) through an ex‐vivo bench study. Methods and results: We assessed SAPIEN and SAPIEN XT THVs, sized 23/26 mm and 23/26/29 mm, respectively. The SAPIEN THVs were explanted samples. Valves were expanded to nominal dimensions, and then incrementally overexpanded with balloons sized 1‐, 2‐, and 3‐mm larger than the recommended diameter. When an appropriate sized non‐compliant balloon was not available, a compliant balloon was utilized. Valves underwent visual and radiographic assessment of overexpansion. SAPIEN THVs with labeled size of 23 and 26 mm could be incrementally overexpanded to midvalve (MV) diameters of 26.7 and 27.4 mm, respectively. SAPIENT XT THVs with labeled size of 23, 26, and 29 mm could be incrementally overexpanded to MV diameters of 26.8, 28.3, and 28.8 mm, respectively. The desired degree of overexpansion was only achieved with use of non‐compliant balloons and not with compliant balloons. The outflow of the SAPIEN and SAPIEN XT had larger diameters than the MV and inflow of the THV. Conclusion: Overexpansion of older generation SAPIEN and SAPIEN XT THVs is possible. Achieving the desired degree of overexpansion was only achieved with use of non‐compliant balloons. This has potential implications for the treatment of failed THVs.